RESTFUL WEB SERVICE IMPLEMENTATION USING SPRING FRAMEWORK IN ROOM ASSETS MANAGEMENT SYSTEM - Syahren Aulia Achsan; Yerymia Alfa Susetyo (Informatika, Universitas Jenderal Soedirman, 2022)
Room is an asset owned by every agency and company. The ability to process information about data of an asset is very important in order to improve performance and efficiency of an agency or company. Good room management skills are needed by every agency and company. Manual room management activities that are still carried out conventionally with paper media are considered less effective and efficient,, so that room management system is needed. In this research, a room management system is created in order to solve that problem. The room management system is built by implementing RESTful web service using Spring framework. RESTful web service is a technology that can be used to perform system integration and application development with multiplatform base using REST architecture. This research produces a room management system that is can used by admin and user to do room management activities such as borrowing the room, and others.